3(x+6)+3=3+5(x-4)

Simple and best practice solution for 3(x+6)+3=3+5(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+6)+3=3+5(x-4) equation:


Simplifying
3(x + 6) + 3 = 3 + 5(x + -4)

Reorder the terms:
3(6 + x) + 3 = 3 + 5(x + -4)
(6 * 3 + x * 3) + 3 = 3 + 5(x + -4)
(18 + 3x) + 3 = 3 + 5(x + -4)

Reorder the terms:
18 + 3 + 3x = 3 + 5(x + -4)

Combine like terms: 18 + 3 = 21
21 + 3x = 3 + 5(x + -4)

Reorder the terms:
21 + 3x = 3 + 5(-4 + x)
21 + 3x = 3 + (-4 * 5 + x * 5)
21 + 3x = 3 + (-20 + 5x)

Combine like terms: 3 + -20 = -17
21 + 3x = -17 + 5x

Solving
21 + 3x = -17 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
21 + 3x + -5x = -17 + 5x + -5x

Combine like terms: 3x + -5x = -2x
21 + -2x = -17 + 5x + -5x

Combine like terms: 5x + -5x = 0
21 + -2x = -17 + 0
21 + -2x = -17

Add '-21' to each side of the equation.
21 + -21 + -2x = -17 + -21

Combine like terms: 21 + -21 = 0
0 + -2x = -17 + -21
-2x = -17 + -21

Combine like terms: -17 + -21 = -38
-2x = -38

Divide each side by '-2'.
x = 19

Simplifying
x = 19

See similar equations:

| 4p^2+12p+3=0 | | 8e+4-(3+9e)= | | 6.2a+10=72 | | 2m+4m=m | | (12x^2)-8x=0 | | 6x(-12)= | | 5(x+16)=x-8 | | 6(x-1)=16 | | 2x+5x-6=9x-8 | | 2x+4(x-8)=-52 | | 143-4x=5x-136 | | 9.06x+63.42=126.84 | | ln(7x+20)=ln(4x-4) | | (x)=1/2(X) | | 9.06+63.42=126.84 | | 2/5*2/5= | | 7x=2+15y | | 9/10x-3/5=9 | | 10=24+18x | | 4x-12=-12-(-4x) | | (x)=3x-12 | | y-6=31 | | 5/7=0.5/0.3 | | 10=24+6x | | A-4/3=21 | | 7(x-1)-6=3x+4(-2+x) | | 10=6+24x | | 6y+10+42.5+-1.5y=180 | | 2/5x=3/20= | | 4x+9=2y | | X/-9-3 | | 5(3n+3)=8(4n+9)+1 |

Equations solver categories